FAKTOR – FAKTOR YANG MEMPENGARUHI TERLAMBATNYA PENYELESAIAN STUDI PADA MAHASISWA FARMASI UNIVERSITAS SARI MUTIARA INDONESIA - Dwi Nursiti; Sri Ramadhani; Siska Dwi Ningsih; Sepriadin Dakhi (Psikologi Universitas Sari Mutiara Indonesia, 2020)
This research was conducted by the number of students who could not graduate on time, the researchers were interested in finding the factors that caused the decline in student interest in completing the final assignment. This study aims to determine the factors behind the completion of the study for students of the Sari Mutiara Indonesia Pharmacy Study Program. Comparative causal research is a type of research in which research is conducted to determine the causes or reasons of differences in group behavior or individual status. The population in this study were students of the Medan USM-Indonesia pharmacy student study program, who were completing a final assignment or totaling 275 people. In this study the sampling was 15% of the population as follows: 15% x 275 = 41.6 rounded up to 42 people. Data collection techniques use indirect communication techniques, namely by distributing questionnaires. The data analysis technique uses statistical analysis. From the results of the study, the average pharmaceutical study student has the motivation to graduate on time, which is as many as 4 respondents or 9.5% availability of less available sources as many as 25 respondents or 59.5% poor quality as many as 30 respondents or 71.4% of peer groups do not support as many as 10 respondents or 23.8% so it can be concluded that motivation to graduate on time, ability to write scientific papers, availability of resources, thesis guidance quality and peer environment are factors that can influence the late completion of studies for students of the Pharmacy Study Program at Sari Mutiara Indonesia.